Livestock feeds assessment report from Meru county, Kenya - Mwendia, Solomon W.; Ohmstedt, Uwe; Peters, Michael; Notenbaert, An Maria Omer (International Center for Tropical Agriculture, 2020)
Among forty-seven counties in Kenya, we choose Meru County in Kenyan highlands with successful dairy as business oriented. Administratively, Meru is divided into four sub-counties namely- Imenti Central, Buuri, North Imenti and South Imenti. We did livestock feeds assessment in Central Imenti sub-county, involving women and men groups. To narrow down to the specific area, we linked to Meru Dairy Union an umbrella that hosts up to 55 dairy societies in the area. From the list, we discriminated against dairy societies that had some external livestock improvements projects with Alliance of Bioversity and CIAT (ABC) and International Livestock Research Institute (ILRI) or any other non-governmental organization. Meru Union’s knowledge on the societies that had not interacted with external livestock improvement initiatives aided arriving on a dairy society fitting the description. We settled on Githongo Dairy Society. The study aimed to inform the Netherlands funded project: Feed and forage seed business models to support further professionalization of the dairy sector in Kenya and Uganda -2019- 2022.